Stronger color evasive racial ideologies predict lower likelihood of open adoption placement with same-sex couples - Reece, Brian J.; Jenkins, Diana L.; Folger, Austin C.; Shaw, Daniel S.; Neiderhiser, Jenae M.; Ganiban, Jody M.; Leve, Leslie D. (Frontiers in Sociology, 2024)
Although the adoption rate among same-sex couples has been increasing, limited research has focused on factors influencing decision making related to placing children with such couples, particularly from the standpoint of birth mothers. Additionally, there is a gap in the literature regarding how biases may influence birth mothers’ decision to place their child with a same-sex couple. This study sought to examine the association between birth mothers’ racial ideologies and their decision to voluntarily place their children with same-sex couples (n = 29) or mother–father couples (n = 354) during the adoption process. Results indicated that birth mothers with stronger color evasive racial attitudes were significantly less likely to place their children with same-sex couples. The need for additional research about the intersections among various forms of bias in the adoption process and the effect of potential interactions between homophobia and racism are discussed. Suggestions for professionals wishing to minimize homophobic and racist bias are provided.